KONSEP MULTIKULTURALISME DALAM RISALAH ISLAM BERKEMAJUAN MUHAMMADIYAH - Lukman, Dikdik Dahlan; Demetrius Siga, Willfridus (FOCUS, 2024)
This research aims to explore the concept of multiculturalism according to Muhammadiyah, specifically as outlined in the concept of the Progressive Islamic Ideology (Risalah Islam Berkemajuan). The research method employed is discourse analysis with a qualitative approach. The primary source of data is the resolutions of the 48th Muhammadiyah Congress in Surakarta, particularly focusing on the section concerning the Progressive Islamic Ideology (RIB). This study affirms that Islam as understood, practiced, advocated, and propagated by the Muhammadiyah organization is highly accommodating to the concept of multiculturalism, including principles that are fundamental such as creed, movement methodology, and preaching understood by Muhammadiyah.